Alterations of Dynamic Regional Homogeneity in Trigeminal Neuralgia: A Resting-State fMRI Study - Yan, Jianhao; Li, Meng; Fu, Shishun; Li, Guomin; Wang, Tianyue; Yin, Yi; Jiang, Guihua; Lin, Jingzhi; Li, Wuming; Fang, Jin; Tian, Junzhang (Frontiers in Neurology, 2019)
Accumulating evidence from neuroimaging studies has supported that chronic pain could induce changes in brain function. However, few studies have focused on the dynamic regional homogeneity (dReHo) of trigeminal neuralgia (TN). In this study, twenty-eight TN patients and 28 healthy controls (HC) were included. Based on the resting-state fMRI (rsfMRI), we detected abnormalities in dReHo in the TN patients. Patients with TN had decreased dReHo in the left middle temporal gyrus, superior parietal lobule, and precentral gyrus, and increased dReHo in the thalamus. Furthermore, the increase in dReHo in the thalamus was positively correlated with duration of TN (r = 0.485, p = 0.012). These results provide compelling evidence for abnormal resting-state brain activity in TN and suggest that the duration of TN may play a critical role in brain function.